Apuntes sobre el proceso constituyente en Chile - Zegarra Llanos, Irene Jetsabel (Pontificia Universidad Católica del Perú, 2022)
In October 2019, in Chile, a series of protests and demonstrations took place, which promoted the constituent process in that country. As a result, the Constitutional Convention was formed, a body that, after a year of work, created a new constitutional text that will be voted on through a constitutional plebiscite to be held in September of this year. In this context, the purpose of this interview is to analyze and evaluate the most important aspects of the constitutional process.

En octubre del 2019, en Chile, se produjo una serie de protestas y manifestaciones que impulsaron el proceso constituyente en dicho país. Como resultado, se formó la Convención Constitucional, órgano que, tras un año de trabajo, creó un nuevo texto constitucional que será votado mediante un plebiscito constitucional a celebrarse en septiembre del presente año 2022. En este contexto, la entrevista tiene la finalidad de analizar y evaluar los aspectos más determinantes sobre el suscitado proceso constituyente.
Notes on the constituent process in Chile
Keywords: Constitution; Constituent process; Constitutional Convention; State; Constitución; Proceso constituyente; Convención constitucional; Estado; https://purl.org/pe-repo/ocde/ford#5.05.00